2005
DOI: 10.1002/ijc.21254
|View full text |Cite
|
Sign up to set email alerts
|

RNASEL germline variants are associated with pancreatic cancer

Abstract: The RNASEL (encoding ribonuclease L) gene Glu265X mutation has been implicated in familial prostate cancer, and an association between the RNASEL Arg462Gln variant and sporadic and familial prostate cancer, has also been suggested. Because prostate cancer occurs in some familial pancreatic cancer families, we evaluated the role of the RNASEL gene variants Glu265X and Arg462Gln in the etiology of pancreatic cancer. Exon 2 of the RNASEL gene was directly sequenced in the germline of 36 familial and 75 sporadic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Several genetic polymorphisms (involving missense mutations in the RNASEL gene) associated with prostate cancer are shown: M1I [19]; a four-nucleotide deletion at codon 157 [23], a truncating mutation E265X [19,24,25], R400P [25], R462Q [19,24,26] and D541E [26]. In addition, R462Q has also been associated with aggressive tumours in familial pancreatic cancer [27] but also retroviruses such as the HTLV type II. The precise pathogenesis of chronic fatigue syndrome remains unknown, although microbial infections could trigger and perpetuate the disease [34].…”
Section: Xmrv In Chronic Fatigue Syndromementioning
confidence: 96%
“…Several genetic polymorphisms (involving missense mutations in the RNASEL gene) associated with prostate cancer are shown: M1I [19]; a four-nucleotide deletion at codon 157 [23], a truncating mutation E265X [19,24,25], R400P [25], R462Q [19,24,26] and D541E [26]. In addition, R462Q has also been associated with aggressive tumours in familial pancreatic cancer [27] but also retroviruses such as the HTLV type II. The precise pathogenesis of chronic fatigue syndrome remains unknown, although microbial infections could trigger and perpetuate the disease [34].…”
Section: Xmrv In Chronic Fatigue Syndromementioning
confidence: 96%
“…As prostate cancer occurs in some familial pancreatic families, Bartsch and co-workers evaluated the role of two variants of RNASEL gene: E265X and R462Q in the etiology of pancreatic cancer [141]. That study showed that the RNASEL R462Q variant might be associated with an increased risk for sporadic pancreas cancer and with more aggressive tumors in familial pancreatic cancer.…”
Section: ) Pancreatic Cancer and Colorectal Cancermentioning
confidence: 99%
“…Promising results were obtained for variants in NAT2 , RNASEL , GSTM1, IL-4, MPO, SOD2, XPC and UGT1A7, the latter possibly interacting with smoking [47][48][49][50][51][52][53] . At the same time, negative results have been reported for mostly non-synonymous coding SNPs in NAT1 , NAT2, GSTM1 , GSTT1 , NAD(P)H , NQO1 , UGT1A7 , UGT1A9 , ARP , SPINK1 , CFTR , CYP1A1 , CYP2D6 , CYP2E1, HFE [47,49,[54][55][56][57][58] .…”
Section: Other Studiesmentioning
confidence: 99%